gajananiari@gmail.com - Gundewadi, Gajanan; Bhimappa, BB; Rudra, Shalini Gaur (Annals of Agricultural Research, 2018)
Attempts to prolong the shelf life of ivy gourd, a medicinally important member of the cucurbitaceae family have been made through use of edible coating. Guar gum and alginate coating was applied at commercial maturity stage. The physiological, textural and sensory parameters for the vegetables under storage at room temperature conditions (22 Â± 2ÂºC and 90-95% relative humidity (RH) were monitored. Edible coating technique was found effective in retarding the physiological maturation and senescence. Guar gum coating was found more effective in reducing PLW (27.5%) and textural firmness (31.7%). Acidity of coated ivygourd was found to increase with maturity, however coated ivy gourd retained its fresh like colouration and flavor even after 9 days of storage at ambient temperatures